Solution Stirring Design Using Magnetic Stirrer on DC Motor with PLC-Based PID Method - Natawangsa, Hari; Furizal, Furizal; Ma'arif, Alfian; A. Salah, Wael (Jurnal Ilmiah Teknik Elektro Komputer dan Informatika, 2025)
Along with the development of the times, the industrial and manufacturing world also develops. One of the activities that is widely carried out in the industrial and manufacturing world is stirring production raw materials, either in the form of solutions or liquids. The purpose of the stirring process is to get a perfectly mixed (homogeneous) stirring. For this reason, a device is needed that can stir the solution as desired. One type of tool that can be used is a magnetic stirrer placed on a DC motor. However, when the DC motor is given a load, the DC motor tends to become unstable so a controller is needed. To solve this problem used PID controller. PID controllers use control constants in the form of PB, Tick, and Tdk. To obtain the controlling constant, a process of trial and error is carried out. The most stable results obtained from the testing process were PB = 600%, Tik = 1.2 s, and Tdk = 0.2 s. With system response in the form of rise time 0.7778 s, peak time = 5s. settling time 5.4286 s, overshoot = 2.8571 RPM and steady state error = 0%. The setpoint used is 700 RPM with a sampling time of 60 ms. The developed system successfully achieves stable and well-controlled stirring. The results of this research contribute to the improvement of solution stirring processes in the industrial and manufacturing domains. The developed system can be effectively utilized for stirring solutions, enhancing the efficiency and quality of production processes.